Study on MR damper for semiactive vibration control - Ang, Wee Lin (2009)
A new Hysteretic Arctangent Model was proposed to model the performance characteristics of a MR damper. The new model gives piecewise smooth characteristics for the MR damper and gives a more accurate representation of the damper characteristics comparing with the other existing models. The MR damper was then studied based on the damper model developed and applied to semiactive control of vehicle suspension system. A quarter car model was used in the computational simulation. Several control strategies - both passive and semiactive ones - were discussed and the results from simulation were evaluated for each control strategy.